Manajemen Pendidikan Dengan Strategi Sistem Informasi Dalam Aktivitas Pengembangan Potensi Diri Siswa Era Society 5.0 - Alivia Fitri Salsabila; Muhammad Atma Taher; Rehnaningtyas Rehnaningtyas (Universitas Maritim AMNI Semarang, 2023)
This study aims to find out how Educational Management with Information System Strategies in the Self-Potential Development Activities of Students in Era Society 5.0. Qualitative methods were used for this useful research. Data collection techniques are observation, in-depth documentation, and interviews. Based on research results and discussions. The stages of planning, organizing, directing, and implementing, as well as controlling, are all included in the school management study. Because the education management information system is an operational force under the progress of formal and informal educational institutions, it is clear that education management is one of the most important and most needed aspects of education in the era of information system development. Good education management methods applied in schools are focused on the factors that make it possible for schools to be popular, superior, and achievers, among others. Forms of self-potential development in students, and teachers include providing extensive guidance to students, helping students who are less involved and motivated to learn, being a good role model, and planning extracurricular activities.